2016
DOI: 10.1111/pere.12114
|View full text |Cite
|
Sign up to set email alerts
|

Self‐esteem and caregiving in romantic relationships: Self‐ and partner perceptions

Abstract: Self-esteem may be associated with romantic partners' experience of emotional support and caregiving. Using a sample of 6,385 heterosexual couples in committed relationships gathered from the RELATionship Evaluation (RELATE) data set (see www.relate-institute.org), structural equation modeling was used to compare two actor-partner interdependence models examining the associations between both partners' self-esteem and perceptions of partner caregiving responsiveness (i.e., accessibility, responsiveness, and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 26 publications
2
9
1
Order By: Relevance
“…As for (i), we found direct effects between low self-esteem and the average levels of the relationship components as well as between both anxious and avoidant attachment and the average levels; we found no direct effects between neuroticism and the average levels of relationship components. Specifically, for low self-esteem, and in line with previous research (Knapp et al, 2016), we found that lower self-esteem was related to the target's lower average level of perceived responsiveness. This finding might be due to the partner's actual lower responsiveness, as shown in a recent study (Cortes & Wood, 2018).…”
Section: Mediationsupporting
confidence: 90%
See 1 more Smart Citation
“…As for (i), we found direct effects between low self-esteem and the average levels of the relationship components as well as between both anxious and avoidant attachment and the average levels; we found no direct effects between neuroticism and the average levels of relationship components. Specifically, for low self-esteem, and in line with previous research (Knapp et al, 2016), we found that lower self-esteem was related to the target's lower average level of perceived responsiveness. This finding might be due to the partner's actual lower responsiveness, as shown in a recent study (Cortes & Wood, 2018).…”
Section: Mediationsupporting
confidence: 90%
“…Low self-esteem Self-esteem, defined as the subjective evaluation or appraisal of the self (Donnellan, Trzesniewski, & Robins, 2011;Leary & Baumeister, 2000), has a far-reaching impact on romantic relationships. In regulating the dependence on their partner (S. L. Murray et al, 2000), people with low self-esteem tend to doubt their partners' positive regard (S. L. Murray, Holmes, & Griffin, 1996a, 1996b, which also manifests in the daily context of a romantic relationship: In terms of emotional relationship components, people with low self-esteem tend to report lower partner caregiving responsiveness, expressed as reporting their partners to be less accessible, responsive, and engaged (Knapp et al, 2016). As for cognitive relationship components, people with low self-esteem are more apt to perceive their partner negatively and to expect that they (the target person) will experience emotional hurt (S. L. Murray et al, 1996aMurray et al, , 1996bMurray et al, , 2000.…”
Section: Neuroticismmentioning
confidence: 99%
“…Responsiveness demonstrates attunement and specific awareness to one's marital or dating partner (Reis & Clark, ). People can be responsive by using comfort words (Kane, McCall, Collins, & Blascovich, ), offering emotional support (Slatcher, Selcuk, & Ong, ), engaging in conversation, and showing accessibility to their partner (Knapp et al, ).…”
Section: Research On Relationship Maintenancementioning
confidence: 99%
“…Responsiveness can also help facilitate effective communication and reduce the possibility of conflict among dating couples (Gordon & Chen, ; Hubbard, ). Moreover, having a partner who is more responsive is positively related to self‐esteem, relationship stability among dating and married partners (Knapp, Durtschi, Clifford, Kimmes, Barros‐Gomes, & Sandberg, ), positive and negative affect, lower reports of depressive symptoms, less marital risk (Slatcher, Selcuk, & Ong, ), greater relationship desire (Birnbaum et al, ), and increased sexual interest (Birnbaum & Reis, ).…”
Section: Research On Relationship Maintenancementioning
confidence: 99%
“…35 In the self-concept mode: symptoms of depression, 36 anxiety, 35 emotional stress, 36 somatization, 37 low self-esteem, 38 constant worry, feelings of uncertainty, 39 anger, guilt, 40 resentments, sadness, 35 feeling of frustration, [41][42] of burden, [43][44] feeling of lack of control over one's own life, 45 among others. In the role function mode: role conflict, 9 dissatisfaction with caregiver role.…”
Section: Family Caregivers From the Perspective Of Roy's Adaptation Mmentioning
confidence: 99%